Optimal dose of fenfluramine in adjuvant treatment of drug-resistant epilepsy: evidence from randomized controlled trials - Xu, Yingchun; Chen, Deng; Liu, Ling (Frontiers in Neurology, 2024)
Objective: Several clinical trials have suggested that fenfluramine (FFA) is effective for the treatment of epilepsy in Dravet syndrome (DS) and Lennox-Gastaut syndrome (LGS). However, the exploration of its optimal target dose is ongoing. This study aimed to summarize the best evidence to inform this clinical issue. Materials and methods:We searched PubMed, Embase (via Ovid), and Web of Science for relevant literature published before December 1st, 2023. Randomized, double-blind, placebo-controlled studies that evaluated the efficacy, safety, and tolerability of FFA in DS and LGS were identified and meta-analysis was performed according to doses. The study was registered with PROSPERO (CRD42023392454). Results: Six hundred and twelve patients from four randomized controlled trials were enrolled. The results demonstrated that FFA at 0.2, 0.4, or 0.7 mg/kg/d showed significantly greater efficacy compared to placebo in terms of at least 50% reduction (P < 0.001, P < 0.001, P < 0.001) and at least 75% reduction (P < 0.001, P = 0.007, P < 0.001) in monthly seizure frequency from baseline. Moreover, significantly more patients receiving FFA than placebo were rated as much improved or very much improved in CGI-I by both caregivers/parents and investigators (P < 0.001). The most common treatment-emergent adverse events were decreased appetite, diarrhea, fatigue, and weight loss, with no valvular heart disease or pulmonary hypertension observed in any participant. For dose comparison, 0.7mg/kg/d group presented higher efficacy on at least 75% reduction in seizure (P=0.006) but not on at least 50% reduction. Weight loss (P=0.002), decreased appetite (P=0.04), and allcause withdrawal (P=0.036) were more common in 0.7mg/kg/d group than 0.2mg/kg/d.There was no statistical difference in other safety parameters between these two groups.The higher range of the licensed dose achieves the optimal balance between efficacy, safety, and tolerability in patients with DS and LGS.